Development of Technology-Integrated Problem-Based Learning Teaching Materials to Improve Critical Thinking Skills in Elementary School Students - Jauziati, Baiq; Waluyo, Edy; Badarudin, Badarudin (IJE : Interdisciplinary Journal of Education, 2025)
This study aims to develop technology-integrated Problem Based Learning (PBL) teaching materials for Natural and Social Sciences (IPAS) to improve the critical thinking skills of elementary school students. The research model used is research and development (R&D) with reference to the 4-D model (Define, Design, Develop, and Disseminate). The research subjects were fourth-grade students at SDN 1 Bagik Payung and SDN 1 Terara. Data collection instruments included tests (pretest-posttest) and non-tests (expert validation questionnaires, student and teacher response questionnaires, and observations). The validation results showed that the teaching materials received a “Very Good” rating from technology experts, subject matter experts, and language experts. The small-scale pilot test demonstrated an average score increase from 59 to 88 at SDN 1 Bagik Payung and from 58 to 85 at SDN 1 Terara, with a moderate N-Gain category. The large-scale pilot test resulted in an average score increase from 57.33 to 89.33 at SDN 1 Bagik Payung and from 56.84 to 88.95 at SDN 1 Terara, with a high N-Gain category. Student and teacher responses to the product were also in the “Very Good” category. Thus, the PBL-based instructional materials integrated with technology developed have proven to be effective, feasible, and usable for enhancing elementary school students' critical thinking skills.